Estabilidade do antígeno de célula total de Brucella abortus para uso no diagnóstico sorológico da brucelose bovina pela reação de fixação de complemento - Mathias, Luis A. [UNESP]; Meirelles, Raphaella B. [UNESP]; Buchala, Fernando G. [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2007)
A reação de fixação de complemento é um dos testes usados no diagnóstico confirmatório da brucelose bovina, e para sua realização emprega-se o mesmo antígeno usado na prova de soroaglutinação lenta, porém não foi possível encontrar na literatura estudos sobre a estabilidade desse antígeno para uso na prova de fixação de complemento, de modo a estabelecer um prazo de validade para o mesmo. Por isso, esta investigação teve por objetivo avaliar a estabilidade do antígeno de célula total de Brucella conservado sob refrigeração, para uso na reação de fixação de complemento. Analisaram-se 14 partidas de antígeno, preparado com Brucella abortus amostra 1119/3 e padronizado para uso na prova de soroaglutinação lenta, com tempo de fabricação variando de 9 meses a 23 anos e 11 meses. Testaram-se 167 soros bovinos com títulos variáveis de anticorpos contra Brucella, adotando-se a técnica com incubação a 37ºC nas duas fases da reação e 5 unidades hemolíticas 50% de complemento. Considerou-se como positivo o soro com pelo menos 25% de fixação de complemento na diluição 1:4. Compararam-se os resultados obtidos com as 13 partidas de antígeno com aqueles obtidos com a partida com 9 meses de fabricação, usando o teste de chi2 de McNemar e o coeficiente kappa. A grande maioria dos soros apresentou resultados muito próximos quando testados com as diversas partidas de antígeno, e não se observou relação entre tempo de fabricação do antígeno e diferenças nos resultados obtidos.

The complement fixation test is used worldwide in the confirmatory diagnosis of bovine brucellosis. For this technique the antigen is the same as the one used in the tube agglutination test. However, literature is poor in information about the stability of the whole cell Brucella antigen for use in the complement fixation test to establish a time of validity of the antigen. Hence the aim of this investigation was to evaluate the stability of this antigen under refrigeration for use in the complement fixation test. Fourteen batches of antigen prepared with Brucella abortus strain 1119/3, produced from 9 months to 23 years and 11 months before, were analysed. One hundred and sixty-seven cattle sera with varying titres of antibodies to Brucella were tested through the warm complement fixation microtechnique with five 50% haemolytic units of complement. Sera with at least 25% of complement fixation in dilution 1:4 were considered positive. The results with 13 of the antigen batches were compared with the results obtained with the batch produced 9 months before by the McNemar chi2 test and kappa statistic. The oldest antigen batch gave a higher proportion of sera titres which were exactly the same observed with the 9-month-batch (90.4%), and the antigen produced 4 years and 3 months before the test gave de lowest proportion of sera with the same titre of the 9-month-antigen (73.7%). The comparison of the results after being classified as positive and negative showed that the highest proportion of agreed results was observed with the antigen produced 21 years and 4 months before (98.8%, kappa 0.98). The antigen with the lowest proportion of agreed results was the one produced 3 years and 2 months before (91.6%, kappa 0.84). The results of the study show that most sera gave very similar results with all antigen batches evaluated, and that there was no relationship between the period of antigen production and the difference in test results.
Stability of Brucella abortus whole cell antigen for use in the serological diagnosis of bovine brucellosis by the complement fixation test
Keywords: Bovine brucellosis; serological diagnosis; complement fixation test; Brucelose bovina; diagnóstico sorológico; Reação de fixação de complemento